Revisiting the concept of incretin and enteroendocrine L-cells as type 2 diabetes mellitus treatment. (June 2022) - Lok, Kok-Hou; Wareham, Nicholas J.; Nair, Rajesh Sreedharan; How, Chee Wun; Chuah, Lay-Hong
Abstract: The significant growth in type 2 diabetes mellitus (T2DM) prevalence strikes a common threat to the healthcare and economic systems globally. Despite the availability of several anti-hyperglycaemic agents in the market, none can offer T2DM remission. These agents include the prominent incretin-based therapy such as glucagon-like peptide-1 receptor (GLP-1R) agonists and dipeptidyl peptidase-4 inhibitors that are designed primarily to promote GLP-1R activation. Recent interest in various therapeutically useful gastrointestinal hormones in T2DM and obesity has surged with the realisation that enteroendocrine L -cells modulate the different incretins secretion and glucose homeostasis, reflecting the original incretin definition. Targeting L -cells offers promising opportunities to mimic the benefits of bariatric surgery on glucose homeostasis, bodyweight management, and T2DM remission. Revising the fundamental incretin theory is an essential step for therapeutic development in this area. Therefore, the present review explores enteroendocrine L -cell hormone expression, the associated nutrient-sensing mechanisms, and other physiological characteristics. Subsequently, enteroendocrine L -cell line models and the latest L -cell targeted therapies are reviewed critically in this paper. Bariatric surgery, pharmacotherapy and new paradigm of L -cell targeted pharmaceutical formulation are discussed here, offering both clinician and scientist communities a new common interest to push the scientific boundary in T2DM therapy. Graphical Abstract: ga1